Effectiveness of Telenursing as Psychoeducation on Family Burden and Knowledge Level on Schizophrenia Patient: A Literature Review - Putu Cintariasih; Ni Putu Kamaryati; Ida Ayu Putri Wulandari; Sarah Kartika Wulandari (GLOBAL HEALTH SCIENCE GROUP, 2024)
Schizophrenia patients often experience significant challenges in daily functioning, leading to dependence on caregivers and imposing a substantial burden on families. This literature review aims to examine the effectiveness of telenursing-based psychoeducation in improving family knowledge and reducing family burden in the care of schizophrenia patients. A comprehensive literature review was conducted, analyzing 15 articles published between August 2014 and August 2024. Articles were sourced from Google Scholar and PubMed for English-language studies, and Google Scholar for Indonesian-language studies. The PRISMA framework and PICO methodology guided the selection and analysis of relevant studies. The findings from the 15 selected articles demonstrate that telenursing-based psychoeducation effectively reduces family burden and enhances caregivers' knowledge in managing schizophrenia patients. Various approaches, including telenursing interventions, technology-based applications, and traditional psychoeducation methods, provide significant benefits and can be integrated into mental health care practices. The successful implementation of telenursing-based psychoeducation requires active commitment, resilience, and collaboration from both nurses and family members involved in the care of schizophrenia patients.